A systematic technical survey of DTN and VDTN routing protocols - Gonçalves Filho, João; Patel, Ahmed; Lopes Alcantara Batista, Bruno; Celestino, Joaquim (Computer standards and interfaces, 2016)
There are major challenges in establishing effective communications between nodes in Vehicular Ad Hoc Networks (VANETs). In them the systems are subject to wireless interference and disconnections, thus hindering the availability and reliability of source-destination connections. Another major problem arises when VANETs are sparse, causing excessive retransmissions and delays due to long periods without maintaing connection between pair of vehicles. In these environments traditional routing protocols proposed for VANETs suffer from the absence of end-to-end connections. From intensive studies and analysis, it was found that these problems are best overcome by using Delay Tolerant Network (DTN) routing protocols that can endure huge delays, connection disruptions and embolden applications to use a minimum number of roundtrip response confirmations. DTN routing protocols are considered to be the most suitable alternative to traditional routing protocols in VANET environments. They are designed for storing and forwarding messages through a series of forwarders to maintain network connectivity. Thus, we present a systematic technical survey and a comparative analysis of a taxonomy of DTN routing protocols, which we extended and adapted it to include a new set of VDTN (VANET/DTN) routing protocol categories with results. •The work outlines several DTN routing protocols.•A taxonomy that includes the VANET category•Two comparative tables of DTN routing protocols•Results of VDTN protocols